Force Entrepreneurship in Contemporary Russia. Part 6: Gangsters and Capitalists - ВолковВадим Викторович (Journal of Economic Sociology, 2010)
The author analyzes the economic policy of the crime groups and the career of a force entrepreneur with the help of case studies. The examples of Tambov and Uralmash groups are given to illustrate the evolution of the informal force structures.